2020
DOI: 10.31557/apjcc.2020.5.2.113-118
|View full text |Cite
|
Sign up to set email alerts
|

Awareness about Gynecological Cancers amongst Tribal Females

Abstract: Background: Gender differences are engrained in our culture and are evident when perceiving women’s health and ill health. Health issues of women are of great importance in a society as it directly impacts the fabric of family and society. With limited access to education or employment, high illiteracy rates and increasing poverty levels health improvements for women are quite difficult in developing countries including India. There is a significant lack of official data on gynecological cancers further for wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
(9 reference statements)
0
2
0
2
Order By: Relevance
“…Yapılan çalışmalarda benzer şekilde JKFÖ puan ortalamasının iyi düzeyde 20,21 olduğu gibi bazı çalışmalarda jinekolojik farkındalıklarının daha düşük olduğu bildirilmiştir. 7,20,22 Yine JKFÖ alt boyutları da literatürle benzerlik göstermektedir. 5,7,22 JKFÖ alt boyutlarından JKETBF yüksek bulunmuştur.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Yapılan çalışmalarda benzer şekilde JKFÖ puan ortalamasının iyi düzeyde 20,21 olduğu gibi bazı çalışmalarda jinekolojik farkındalıklarının daha düşük olduğu bildirilmiştir. 7,20,22 Yine JKFÖ alt boyutları da literatürle benzerlik göstermektedir. 5,7,22 JKFÖ alt boyutlarından JKETBF yüksek bulunmuştur.…”
Section: Discussionunclassified
“…7,20,22 Yine JKFÖ alt boyutları da literatürle benzerlik göstermektedir. 5,7,22 JKFÖ alt boyutlarından JKETBF yüksek bulunmuştur. Dal ve ark.…”
Section: Discussionunclassified
“…Maharashtra reported that the majority of the women have not heard of cervical (80%) and breast cancer (64%) (Jha et al, 2020). Primary care physicians are the first point of contact for these marginalized communities and act as a custodian for providing health-related information and referral for cancer care to these populations.…”
Section: Introductionmentioning
confidence: 99%
“…A cross-sectional study on awareness of gynaecological cancers amongst tribal females in Borivali, Mumbai city found a signi cant lack of awareness about the symptoms, treatment, and preventive measures. Poor awareness was responsible for limited access to education and employment, high illiteracy rates, and increasing poverty levels [15]. An online survey on the association between demographic factors and reproductive cancer awareness in India found that gender, knowledge of screening tests, and marital status were all signi cantly associated with awareness of reproductive cancer [16].…”
Section: Introductionmentioning
confidence: 99%